Determination of hand grip and pinch strength among young adult Malaysian students in a public university in Malaysia - Saad, Nancy Mohammed Ahmed (2018)
Grip strength indicates the description of the status and general muscle strength of hand and overall upper extremity strength. It is an important measure used to evaluate outcomes of treatment after injured hands. Currently, there are not any established local data regarding grip strength norms. As such, these norms should be developed for various nationalities living in the same or different geographical region. The aim of the present study is to determine the hand grip and pinch strengths and its associated factors among Malaysian students in Universiti Putra Malaysia. A cross-sectional study using multistage random sampling was carried out among Malaysian students aged 18-29 years in Universiti Putra Malaysia from November 2017 until April 2018. The sample size was 848 respondents based on two group mean comparison formula. Data was collected using Structured questionnaire on sociodemographic characteristics, medical history, lifestyle practices, and measurements, including anthropometry and handgrip strength were taken. Data collected coded and analyzed using IBM SPSS software. Data was analyzed using descriptive and analytical statistics. Pearson correlation test was used to examine the relationship between hand grip strength and pinch grip strength. The results show that the overall response rate was 94% . Majority of the respondents were Malays (81.6%) followed by Chinese (12.4%) and finally Indian (6%). The overall mean age was 21.05 ±sd= 1.79 years and ranged between 18 and 29 years. The overall mean hand grip strength (HGS) was 18.32 (±sd=5.99) kg and ranged between 8.17 to 41.0. The mean hand grip strength (HGS) for male students was 24.74 (±sd=7.66) kg and ranged between 11.50 to 41.00. While the overall mean HGS among female students was 16.94 (±sd=7.66) kg and ranged between within 8.17 to 30.67. In Conclusion there was a significant relationship between hand grip strength and socio-demographic characteristics (age, gender, ethnicity, BMI and hand dominance). There was a significant association between BMI and pinch grip strength in terms of (KP, PP, TP) in both right and left hands. Gender, BMI, ethnicity and age are predictor factors that affecting hand grip strength. Three predictor factors which are gender, BMI and ethnicity were affecting key pinch and palmar pinch strengths. While only two predictors factors which are gender and BMI were affecting tip pinch.